FEATURES OF TAX POLICY IN THE STATE OF HERAT AT THE END OF THE 15th CENTURY (DURING THE REIGN OF HUSAYN BAYQARA) - Turdaliyeva G. А. (TARIXIY TADQIQOTLAR, 2026)
This article analyzes the fundamental principles of tax policy implemented in the Herat state at the end of the 15th century, using the reign of Husayn Bayqara as a case study. The research examines the formation of the tax system during the Timurid period, the types of taxes, the procedures of their collection, and their role in state financial administration. Particular attention is paid to Husayn Bayqara`s economic policy and the measures aimed at establishing a fair tax system, as well as their impact on social and economic life. Based on historical sources, the article also evaluates the significance of tax policy in the context of centralized state governance and urban development. The findings contribute to a deeper understanding of the financial management system of the Timurid era.